2133.6 centimeters i hope i help you
Answer:
x² + 3x - 28
Step-by-step explanation:
Each term in the second factor is multiplied by each term in the first factor
(x + 7)(x - 4)
= x(x - 4) + 7(x - 4) ← distribute both parenthesis
= x² - 4x + 7x - 28 ← collect like terms
= x² + 3x - 28
Answer:
b<58/5
Step-by-step explanation:
We have that
the expression 2f + 4f + 2 – 3-------> we can group it (2f+4f)+(2-3)
(2f+4f)+(2-3)=(6f-1)
therefore
the expression [2f + 4f + 2 – 3] is equivalent to [6f-1]
if the expression [6f-1] for f=3 is 17
then
the expression [2f + 4f + 2 – 3] for f=3 is also 17
<span>let's check it
</span>[2*3 + 4*3 + 2 – 3]--------> [6+12+2-3]=[20-3]=17------> is ok